Remittance of Myanmar Migrants - อินทุฤทธิ์, ดนัยกฤต (Journal of Social Sciences and Humanities Research in Asia, 2019)
This study aims to analyze 1) volume and frequency of remittance, and 2) factors effecting remittance of Myanmar migrant workers. Data was collected by a questionnaire with 400 samples of Myanmar migrant workers living in Chiang Mai province. A path analysis was used to analyze the motivational factors effecting remittance. The result indicated that 339 of Myanmar workers remitted home at an average annual remittance of 10,709.73 Baht. They averagely remitted at 5.57 times per year. They also remitted at 1,922.75 Baht per person. Each of them paid for remittance expenditures at 243.85 Baht per year. While debts affected both direct and indirect effects of motivational remittance factors. This research suggests that Thai financial institutions should reduce the fees for remittance in order to attract the migrant workers to remit money back home through Thai financial institutions instead of through network of Myanmar people.